Cultural consumption and entertainment in the Covid-19 lockdown in Spain: Orange economy crisis or review? - García, Daniel; Sánchez-Bayón, Antonio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
This is a socio-economic study on the state of cultural industries and entertainment in Spain during the confinement for Covid-19. An analysis is carried out on what type of cultural offer has been consumed, as well as the way and way of doing it. To do this, a group of citizens was interviewed, using a questionnaire, where they were asked about the type of cultural products and services used as entertainment during confinement. Also, the channels managed were investigated, with special attention to streaming platforms and the most used digital tools. Finally, there is a global review.